Flipped classroom: a strategy for implementing active methodologies in times of the Covid-19 pandemic (Research, Society and Development, 2022)
• The flipped classroom is based on the principles of active methodologies, in which the student assumes the main role in the learning process. Thus, this article aims to analyze the use of the flipped classroom, as a strategy for the execution of dialogic presentations, in the subject Literacy and Literacy of the Pedagogy course of PARFOR/UFC during emergency remote teaching, through Google Meet. The research presented is an exploratory-descriptive study, with a qualitative approach. The data collection technique used was the observation of the teacher-trainer's practice in joint action with the students, recorded in a field diary and in recordings, agreed with the teacher-students. As a result, it was evident that the dialogical exposition, from the strategy used, provided significantly the participation of the students in all the proposed actions, with autonomy and creativity, stimulating logical reasoning, critical sense, and interactivity. It was concluded that, with this research, it was possible to understand that with the use of the flipped classroom before the dialogical presentations, the students obtained a better performance, because they participated in the classes more effectively, even during the remote teaching, not compromising their learning process.